THE EFFECT OF PROGRAMME WITH SHOOTING STRAP ON THE ACCURACY OF BASKETBALL SHOOTING (Fiep Bulletin - online, 2014)
Basketball shooting is one of the most important individual skills in basketball. This study empirically assesses the effects of shooting programmes on accuracy of basketball shooting in two groups. The aim of the study is to increase % of shooting accuracy of young players. We expected significant increase % of shooting accuracy in the experimental group.  Significantly greater differences were expected in the experimental group compared to the control group. Two basketball teams underwent on 10 weeks shooting programme. The experimental group (n=11 boys, 12.23±0.49 years), used shooting strap, control group (n=12 boys, 12.10±0.49 years) did not use shooting strap. All shooting attempts were notified during the training programme. The pre-post changes of shooting accuracy in experimental group and control group were assessed by non-parametric Wilcoxon T-test. Differences of experimental and control group were assessed by non-parametric Mann-Whitney U-test. We noticed increase of shooting % between pre-post test of experimental and control group. Result showed that experimental group gained greater differences. We recommend applying shooting  programme with shooting strap to young players.
Keywords: basketball; shooting programme; shooting strap; youth